Green house: New Directions In Sustainable Design - Alshaikh, Ramzi (Latakia University Journal -Engineering Sciences Series, 2019)
في إطار ازدياد الوعي حول قضايا البيئة, والأسباب وراء تفاقم انبعاث الغازات, و الاستنزاف الكبير للموارد الطبيعية غير المتجددة في تشغيل القطاعات السكنية, والتجارية, والصناعية, وغيرها, جاء البحث ضمن مفهوم العمارة الخضراء و متطلبات المباني الصديقة للبيئة, وأهم الأسباب وراء وقوف منظمات البيئة العالمية حول دعم و تطوير آلية توجيه المعماريين و المختصين إلى تبني عمارة قادرة على تحقيق التوازن بين قطاع المباني و بين البيئة الطبيعية المحيطة به, وجعل الموارد المتوفرة في البيئة جزءاً من برنامج التصميم, للتخفيف من التأثير الضار للمباني و القضاء على المدن المريضة. كما يركز البحث على تجارب عالمية تعتمد تصميم المنازل الخضراء الصديقة للبيئة, وتستخدم أحدث التقنيات التكنولوجية المتوفرة, والتي تساعد على تحقيق هدف المصمم في خلق مسكن صحي ملائم للإنسان يمارس به نشاطاته المختلفة برفاهية كاملة و يطبق الاستدامة بكل جوانبها, للاستفادة منها في تطوير الواقع الراهن في مجتمعنا و تحويل مساكننا إلى مبان صحية أكثر ملاءمة. In the framework of the increasing awareness about environmental issues, The reasons behind the worsening greenhouse gas emissions, And the great attrition Of non-renewable natural resources In the operation of residential, commercial, industrial, and other,Research came within the concept of green architecture, And green building requirements, The most important reasons behind the support of the Global Environment organizations About the support and guide the development of architects, and specialists mechanism To adopt the architecture is able to achieve a balance between the buildings sector and between the natural environment surrounding it, And make available resources in the environment part of the design program, to mitigate the adverse impact of the buildings and the elimination of diseased cities. The research focuses on international experiences based green eco-friendly home design, And using the latest technological techniques available, And which help to achieve the goal of the designer in the creation of an appropriate healthy dwelling for a person practiced by the various activities complete the well-being and applied sustainability in all its aspects, For use in the development of the current reality in our society and to transform our housing more convenient healthy buildings.